Analysis of failure of flexible geocell-reinforced retaining walls in the centrifuge. Issue 6 (1st December 2014) - Yang, Y.-F.; Xie, Y.-L.; Yang, X.-H.; Song, F.
Abstract : ABSTRACT: Since the 1980s, flexible geocell-reinforced retaining walls have been used more frequently for slope protection as an alternative to conventional retaining structures. The benefits of these geocell structures include light weight, rapid construction, cost-effectiveness, ecological protection and landscape enhancement. However, the deformation mechanisms and failure modes of geocell-reinforced retaining walls are often complicated, thereby restricting their use in engineering practice. The differences in failure behaviour between geocell-reinforced and rigid-facing retaining walls need to be identified. In the present study, a series of centrifuge model tests on retaining walls reinforced by geocells were performed. The tests varied with respect to aspect ratio (the reinforcement length to the height of the wall) and the slope inclination (horizontal to vertical). The experimental results indicate that the critical failure surface is a non-linear shape that passes through the toe of the wall and intersects with the back of the wall. As the aspect ratio decreased, the horizontal distance between the top of the critical failure surface and the wall increased, whereas the location of the critical failure surface intersecting with the wall moved downward. In the case of a smaller inclination angle, the critical failure plane had a compound shape that included part of the backfill material near the top portion of the wall. In the case of a larger inclination angle, the size of the sliding zone was small and the failure was mainly due to sliding of the wall along the slope. The internal displacement distributions in the sliding zone were measured using digital image analysis and indicated that the locations of the maximum lateral face displacement in geocell retaining walls differs from those in conventional rigid retaining walls.